Anti-Müllerian hormone: plasma levels in women with polycystic ovary syndrome and with premature ovarian failure - Skałba, Piotr; Cygal, Anna (Menopause Review/Przegląd Menopauzalny, 2011)
Background: Anti-Müllerian hormone (AMH) is a member of the transforming growth factor β (TGF-β) family of growth and differentiation factors. AMH is produced by granulosa cells of preantral and small antral follicles. Aim of the study: The aim of the study was to assess the AMH plasma levels of healthy women in reproductive age and in women with polycystic ovary syndrome (PCOS) and premature ovarian failure (POF). Material and methods: The study included 187 women. Results : AMH concentration in serum of patients with PCOS (73.68 ±25.58 pmol/l) was significantly higher than in healthy women (16.97 ±5.80 pmol/l) (p < 0.05). In patients with POF AMH concentrations in blood serum were very low or undetectable, and averaged 0.65 ±1.81 pmol/l. Average concentrations of AMH in the blood serum of the healthy group of patients differed significantly (p < 0.001) between the age-dependent subgroups. AMH concentration in serum of healthy women decreased with age. The average concentration of AMH in the blood serum in PCOS decreased after 30 years of age. There were no statistically significant differences between age subgroups. In the premature ovarian failure patients with secondary amenorrhea persisting for at least three years AMH plasma levels were extremely low (0.16 ±0.10 pmol/l) and showed a significant difference compared to patients whose menses returned. Conclusions : 1. In PCOS women the determination of AMH plasma levels can be used to assess severity of the syndrome. 2. The determination of AMH in blood serum can be used as a marker of diminished ovarian reserve in premature ovarian failure women.